The Importance of the Safety Net Program for Informal Workers’ Food Security Amid the COVID-19 Pandemic in Indonesia - Umaroh, Rodhiah; Amirusholihin, Amirusholihin; Yuliawati, Yuliawati (UI Scholars Hub, 2024)
This study examines the effects of social safety-net programs on food security among vulnerable groups, focusing on households with informal workers. Utilizing data from the High-Frequency Monitoring of the COVID-19 Impacts 2020 (HiFy) and estimates with the Longitudinal Propensity Score Matching (LPSM) method, the findings reveal that cash and food assistance significantly reduce food insecurity among informal workers’ households. The households receiving these safety net programs experienced an 8–11% lower probability of food insecurity compared to non-recipients, as indicated by the Average Treatment Effect on the Treated (ATT) value. The study highlights the need for continued investment in inclusive and effective safety net programs to safeguard vulnerable populations, particularly in developing countries with significant informal labor forces.